HIDROLISIS SELULOSA MENGGUNAKAN KATALIS KARBON TERSULFONASI BERBASIS CANGKANG KEMIRI - Dian Halimah Batubara; Taslim; Seri Maulina; Iriany (Jurnal Teknik Kimia USU, 2018)
Cogon grass (Imperata cylindrica) contains cellulose which is convertible to glucose through hydrolysis by using inorganic liquid acid catalyst. However, the use of such catalyst leads to corrosion problem, environment pollution, and complex separation. To overcome this problem, a sulfonated carbon catalyst was proposed. This study aimed to evaluate candlenut shell as carbon source for catalyst support in sulfonated carbon catalyst, and its application in cellulose hydrolysis. Candlenut shell was carbonized at 300-550oC for 4 h. Resulting carbon was sulfonated at 120-150oC for 6 h. Sulfonated carbon was assessed for its H+ capacity/acidity. The carbon with highest acidity was applied as solid acid catalyst in cogon grass hydrolysis. Resulting glucose was analyzed by dinitrosalicylic acid (DNS) method. Results suggest that sulfonated carbon from candlenut shell can be utilized as heterogeneous catalyst in cogon grass hydrolysis.